Les lignes de force de la Loi 89 instituant un nouveau Code civil et portant réforme du droit de la famille - Longtin, Marie-José (Les Cahiers de droit, 1981)
The family law reform is based upon several principles among which the legislation seeks to create a certain balance. The new legislation approaches the question of that balance under four themes : 1. The equality between man and woman - an equality sometimes intruded upon in order to protect one of the spouses or to strengthen his or her self-determination ; 2. the spouses' freedom to arrange their family relations as they see fit, but a freedom limited by several mandatory rules in order to ensure a greater measure of equality for each ; 3. the equality between children regardless of the circumstances of their birth or their form of filiation - an equality strengthened by rules devised to protect their interests ; 4. the increased intervention of the judiciary authaurised mostly for promotive self-reconciliation by the parties. The following comments try to illustrate how these four principles are embodied in book two of the Civil Code of Quebec, book which must be construed according to the Legislator's expressed view for overriding equality, simplicity and flexibility.